Tinjauan Faktor-faktor Pendorong dan Penghalang Pemindahan Latihan: Konteks Malaysia - Shaharuddin, Balkisnah; Abiddin, Norhasni Zainal (SOSIOHUMANIKA, 2009)
ABSTRACT: Human development and training program are one of the important aspects in developing an organization and to improvise and upgrade the performance of their personnel.Â However, a few research found that 55 billion have been allocated by an organization for the purpose of conducting formal training, but only 10% training transfer occurred at workplace. This was supported by the previous research that indicated multi millions Ringgit were spend every year in training and adult education, but the increase in performance at workplace was only 10%. This article reviews the literatures related to training transfer.Â It will also identify the factors that influence and hinder the process of training transfer to happen. Training transfer has also influenced by these factors such as: (1) individual factor; (2) working environment factor or organizational culture, (3) organizational support factor; and (4) training design factor. This article also explores adult education theories and motivation theories. It is hoped that related to literature review on training transfer could assist us in understanding the relationship among the effectiveÂ training transfer related to factors that could allow the process of transferring training to be continuously implemented and improvement can be done from time to time. Key words: training, model, organization, theory, training transfer, motivation and adult education.Â Â About the Authors: Balkisnah Shaharuddin, M.Sc. ialah pelajar Ph.D. di Jabatan Pemajuan Profesional dan Pendidikan Lanjutan, Fakulti Pengajian Pendidikan (UPM). Menyelesaikan pendidikan B.Sc. (Hons) Kimia di Universiti Sains Malaysia; M.Sc. (Pengurusan) di Universiti Putra Malaysia; Diploma Pendidikan (KPLI), MTRM. Beliau sedang menulis disertasi bertajuk âPemindahan Latihan Bestari dalam Kalangan Guru Sekolah Rendah Bahagian Miriâ. Untuk kepentingan akademik, penulis dapat dihubungi dengan alamat e-mail: kis_miri66@yahoo.com.my Prof. Madya Dr. Norhasni Zainal Abiddin ialah Pensyarah di Jabatan Pembangunan Profesional dan Pendidikan Lanjutan, Fakulti Pengajian Pendidikan, Universiti Putra Malaysia (UPM). Menyelesaikan pendidikan Dip.Sc. di UPM pada 1995; pendidikan B.Sc. dan M.Sc. di universiti yang sama pada tahun 1998 dan 2000; serta program Ph.D di University of Manchester, United Kingdom pada tahun 2004, dengan menulis disertasi bertajuk âEffective Supervision of Research Students: A Study of United Kingdom University Practices and Overseas Studentsâ Experiencesâ. Untuk kepentingan akademik, penulis dapat dihubungi dengan alamat e-mail: nonie@ace.upm.edu.myHow to cite this article? Shaharuddin, Balkisnah & Norhasni Zainal Abiddin. (2009). âTinjauan Faktor-faktor Pendorong dan Penghalang Pemindahan Latihan: Konteks Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.1 [Mei], pp.107-124. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (March 17, 2009); Revised (April 20, 2009); and Published (May 20, 2009).